Two new species of Quadrimaera (Crustacea: Amphipoda: Melitidae) from Atol das Rocas, Brazil - Senna, André R.; Serejo, Cristiana S. (Zootaxa, 2007)
A field collection of Crustacea was made in the Biological Reserve of Atol das Rocas, Northeastern Brazil, from October 2000 to October 2001. Specimens were obtained from washed algae, from the inner and outer parts of the annular reef between 0–20 m depths. In this paper we describe two new species of the genus Quadrimaera Krapp-Schickel & Ruffo, 2000 (Amphipoda: Melitidae) from Atol das Rocas. Quadrimaera chaelata sp. nov. differs from all other species of the genus by a strong process in the palmar corner on the propodus of gnathopod 2 that essentially makes it chelate; Quadrimaera rocasensis sp. nov. differs from its congeners in size, shape, and order of excavations on the palm of gnathopod 2, by a robust spine on the inner margin of the dactylus of gnathopod 2 that opposes the first excavation of the palm, and by three long bifid setae and a nail with an apical seta, in each lobe of the telson. The two new species are endemic to Atol das Rocas. This study raises to three the number of known species of the genus Quadrimaera from the atoll: the two new species and Quadrimaera cristianae Krapp-Schickel & Ruffo, 2000. A key to identification for the species of Quadrimaera from Atol das Rocas is given.